DAMPAK KEGIATAN PERTAMBANGAN PASIR TERHADAP PENDAPATAN KELUARGA PEMILIK TAMBANG DIDESA PETAPAHAN KECAMATAN TAPUNG KABUPATEN KAMPAR - Fitri Qolbina; Hendro Ekwarso; Ufira Isbah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
The purpose of this study was to determine the impact of sand mining operations and mine owners to the family income the village Petapahan Tapung subdistrict Kampar district and to determine whether sand mining in the village Petapahan Tapung subdistrict Kampar district is able to release the mine owners family from poverty. The method used in this research in using the Sign Test analysis and quantitative descriptive analysis method. To complete this study, the author uses primary data obtained by direct communication with the respondent that the sand mine owners in the village Petapahan Tapung subdistrict Kampar district, and secondary data. The sample population is sand mine owner in the village Petapahan Tapung subdistrict Kampar district. Samples ware taken using census sampling method is sampling technique when all the population used as a sample as many as 52 heads of family of mine owners. Of the results of research conducted, shows that sand mining activities have a positive impact on revenue Petapahan mine owners in the village Tapung subdistrict Kampar district. Average income of mine owners before making sand mining activities amounted Rp 2.000.000 – Rp 5.000.000 per month, while the average total income after sand mining operations is amounted Rp 27.314.288 – Rp 30.542.859 per month, mine owners in sand Petapahan village subdistrict Tapung are people above the poverty line. Fixed income Rp 2.000.000 – Rp 5.000.000 per month.Keywords: Sand mining, income, and poverty